Modern Cloud Computing Paradigms and Their Impact on It Infrastructure Optimization (International Journal of Engineering and Computer Science, 2025)
This article analyzes contemporary paradigms of cloud computing and examines their influence on the optimization of IT infrastructures. The study offers a comprehensive review of the literature, tracing the evolutionary stages of computing paradigms—from mainframes to hybrid cloud solutions—and outlines the core models (IaaS, PaaS, SaaS) that underpin modern cloud services. Special attention is given to the benefits of cloud adoption, such as scalability, flexibility, and cost reduction, alongside a critical evaluation of key challenges including security concerns, legacy system integration, vendor lock-in, and regulatory compliance. The article also explores forward-looking developments such as integration with Edge Computing, the Internet of Things, and artificial intelligence, which collectively lay the foundation for further optimization of IT infrastructures in the context of digital transformation. The insights presented here will be of interest to researchers and leading IT professionals engaged in the theoretical analysis and development of modern distributed computing models. Additionally, the findings offer practical value for strategists and practitioners seeking to implement innovative solutions that enhance the efficiency and scalability of enterprise systems within increasingly dynamic technological environments.